Financial performance of shipping firms that increase LNG carriers and the support of eco-innovation - Kian-Guan Lim; Michelle Lim (Journal of Shipping and Trade (JST), 2020)
The technology to liquefy natural gas for transport to countries worldwide and the increasing use of natural gas as a cleaner fossil fuel for industry and household meant that the supply of liquified natural gas (LNG) worldwide is a profitable trend. Shipping companies can strategically choose to diversify into LNG fleet to grasp this trend. By supplying more LNG shipping capacities, the greater availability of LNG worldwide, as a source of marine fuel and as a source of cleaner energy in replacing coal and oil, is supporting eco-innovation. In this paper, we investigate three economic and financial benefits to a shipping firm that diversified into liquefied natural gas (LNG) shipping, namely firm profitability performance, firm efficiency, and stock return performance. We also investigate if there is an early mover advantage in doing so. Our empirical findings indicate that fleet diversification into LNG carriers resulted in higher profitability and better operational efficiency. For the listed shipping firms, their stock returns increased with diversified exposures to the LNG business. There is some evidence of higher profitability in the early mover advantage. Firms that originated in LNG business also benefited when there was diversification into the non-LNG business.
Keywords: 650; Liquefied natural gas carriers; Shipping financial performance; Shipping stock performance